Financial Capability Analysis of Gree Electric Appliances Based on the Harvard Framework - Jiaxin Zhang (Journal of Frontier in Economic and Management Research, 2025)
This study employs the Harvard analytical framework to evaluate Gree Electric’s financial performance across strategy, accounting, finance, and prospects. Results show that Gree leads the industry in profitability and long-term debt repayment capacity, supported by strong R&D and cost control from its vertically integrated model. Sustained innovation has generated extensive patents, enabling high-margin premium products. However, Gree faces constraints due to over-reliance on its core air-conditioning business, declining inventory turnover, and slow overseas expansion. Its diversification into new sectors like new energy and smart equipment remains limited, accounting for under 5% of revenue and failing to mitigate core market risks. Operating cash flow volatility further reflects instability in these new ventures. Strategic recommendations include scaling the new energy segment, enhancing overseas localization, and optimizing supply chain finance. The study also suggests that Gree should focus on green, smart technologies and value-added services to strengthen competitive barriers. Future research could incorporate ESG metrics to improve analytical comprehensiveness.